Association of Endodontic Lesions with Coronary Artery Disease. (November 2016) - Liljestrand, J.M.; Mäntylä, P.; Paju, S.; Buhlin, K.; Kopra, K.A.E.; Persson, G.R.; Hernandez, M.; Nieminen, M.S.; Sinisalo, J.; Tjäderhane, L.; Pussinen, P.J.
An endodontic lesion (EL) is a common manifestation of endodontic infection where Porphyromonas endodontalis is frequently encountered. EL may associate with increased risk for coronary artery disease (CAD) via similar pathways as marginal periodontitis. The aim of this cross-sectional study was to delineate the associations between EL and CAD. Subgingival P. endodontalis, its immune response, and serum lipopolysaccharide were examined as potential mediators between these 2 diseases. The Finnish Parogene study consists of 508 patients (mean age, 62 y) who underwent coronary angiography and extensive clinical and radiographic oral examination. The cardiovascular outcomes included no significant CAD ( n = 123), stable CAD ( n = 184), and acute coronary syndrome (ACS; n = 169). EL was determined from a panoramic tomography. We combined data of widened periapical spaces (WPSs) and apical rarefactions to a score of EL: 1, no EL ( n = 210); 2, ≥1 WPS per 1 apical rarefaction ( n = 222); 3, ≥2 apical rarefactions ( n = 76). Subgingival P. endodontalis was defined by checkerboard DNA-DNA hybridization analysis, and corresponding serum antibodies were determined by ELISA. In our population, 50.4% had WPSs, and 22.8% apical rarefactions. A total of 51.2% of all teeth with apical rarefactions had received endodontic procedures. Subgingival P. endodontalis levels and serum immunoglobulin G were associated with a higher EL score. In the multiadjusted model (age, sex, smoking, diabetes, body mass index, alveolar bone loss, and number of teeth), having WPSs associated with stable CAD (odds ratio [OR] = 1.94, 95% confidence interval [95% CI] = 1.13 to 3.32, P = 0.016) and highest EL score were associated with ACS (OR = 2.46, 95% CI = 1.09 to 5.54, P = 0.030). This association was especially notable in subjects with untreated teeth with apical rarefactions ( n = 59, OR = 2.72, 95% CI = 1.16 to 6.40, P = 0.022). Our findings support the hypothesis that ELs are independently associated with CAD and in particular with ACS. This is of high interest from a public health perspective, considering the high prevalence of ELs and CAD.